Canola/Rapeseed Protein: Future Opportunities and Directions—Workshop Proceedings of IRC 2015 - Campbell, Lisa (Plants (Basel), 2016)
At present, canola meal is primarily streamlined into the animal feed market where it is a competitive animal feed source owing to its high protein value. Beyond animal feed lies a potential game-changer with regards to the value of canola meal, and its opportunity as a high quality food protein source. An economic and sustainable source of protein with high bioavailability and digestibility is essential to human health and well-being. Population pressures, ecological considerations, and production efficiency underscore the importance of highly bioavailable plant proteins, both for the developed and developing world. Despite decades of research, several technologies being developed, and products being brought to large scale production, there are still no commercially available canola protein products. The workshop entitled “Canola/Rapeseed Protein—Future Opportunities and Directions” that was held on 8 July 2015 during the 14th International Rapeseed Congress (IRC 2015) addressed the current situation and issues surrounding canola meal protein from the technological, nutritional, regulatory and genomics/breeding perspective. Discussions with participants and experts in the field helped to identify economic barriers and research gaps that need to be addressed in both the short and long term for the benefit of canola industry.